Use of melatonin: a single-centre audit. Issue 1 (15th February 2022) - Dack, Rebecca; Garstang, Joanna J
Abstract : Sleep disorders in childhood are common. Melatonin is prescribed by UK community paediatricians to treat sleep disorders, but practice is not standardised. This audit reviewed melatonin prescribing within a community paediatric department in a 12-month period. 682 children received melatonin prescriptions; a random sample of 198 records were reviewed. The most common underlying condition was autism spectrum disorder (ASD) in 28%. 41% had no underlying diagnosis when melatonin was initiated and were waiting for neurodevelopmental/ASD assessment. 42% were on melatonin for at least 2 years. Further work is required to optimise melatonin prescribing practice for children and young people.